PEMBELAJARAN DAN PENGEMBANGAN PERSONAL BRANDING DI MEDIA SOSIAL PADA GENERASI Z - Sari, Wulan Purnama; Irena, Lydia; Augustine, Michelle; Carolina, Alexandra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Goodstat projects that by 2026, around 81.82% of Indonesia's population will have a social media account. This percentage has doubled compared to the figure in 2017. Apart from that, the data also reflects that the average age of social media users in Indonesia is over 18 years. By referring to this information, it can be concluded that the majority of social media users are generation Z, namely the group of individuals born between 1995-2010, which is also known as the digital native generation. Generation Z will have a very important role in the future development of society, especially as the next generation in Indonesia. In a competitive era like now, the number of individuals with similar skills is increasing. Therefore, it is important to build personal branding to introduce one's skills so that they stand out from others. The development of personal branding can improve a person's self-image based on their skills and reputation. Therefore, the solution to the problem above is exposure to the younger generation, in this case Santo Yakobus High School students, regarding learning and developing personal branding on social media. PKM is carried out using the seminar method. This method is applied as the most effective form of presenting personal branding in which discussions can be held with students, and ends with suggestions and evaluation. The mandatory output of this research is the proceedings at a scientific meeting, while the additional output is the recording of IPR. The PKM activities were carried out smoothly and the students enthusiastically asked questions. The PKM team also carried out measurements before and after the activities to determine the effectiveness of the material provided. The measurement results show an increase in PKM activity participants, students, in terms of personal branding, especially on social media. ABSTRAK Data yang diperoleh dari Goodstat menuliskan bahwa pada tahun 2026, 81,82% orang Indonesia akan memiliki akun media sosial. Jumlah ini meningkat dua kali lipat dibandingkan dengan angka pada tahun 2017. Data juga menunjukkan bahwa pengguna media sosial Indonesia rata-rata di atas 18 tahun. Berdasarkan data tersebut dapat disimpulkan bahwa generasi Z, yang juga dikenal sebagai generasi digital native yang lahir antara tahun 1995 dan 2010, adalah mayoritas pengguna media sosial. Generasi Z akan memainkan peran yang signifikan dalam pembangunan masyarakat di masa depan, terutama sebagai generasi penerus di Indonesia. Dalam era yang kompetitif seperti sekarang, jumlah individu dengan keterampilan yang serupa semakin meningkat. Maka dari itu penting untuk membangun personal branding guna memperkenalkan keterampilan seseorang agar lebih menonjol dibandingkan dengan yang lain. Pengembangan personal branding tersebut mampu dapat meningkatkan citra diri seseorang berdasarkan keterampilan dan reputasi yang dimilikinya. Maka dari itu, solusi dari permasalahan di atas adalah pemaparan terhadap generasi muda, dalam hal ini siswa SMA Santo Yakobus, terkait pembelajaran dan pengembangan personal branding di media sosial. PKM dilaksanakan dengan metode seminar. Metode ini diaplikasikan sebagai bentuk yang paling efektif dalam pemaparan personal branding di mana di dalamnya dapat dilakukan diskusi dengan siswa, serta diakhiri dengan saran dan evaluasi. Luaran wajib dari penelitian ini adalah prosiding dalam temu ilmiah, sedangkan luaran tambahannya adalah pencatatan HKI. Kegiatan PKM dilaksanakan dengan lancar dan para siswa antusias bertanya, tim PKM juga melakukan pengukuran sebelum dan sesudah kegiatan untuk mengetahui efektivitas dari materi yang diberikan. Hasil pengukuran menunjukkan adanya